セールロンダーネ サンチ チガク チョウサ タイ ホウコク 1990/91(JARE-32) - 岩田, 修二; イワタ, シュウジ; 白石, 和行; シライシ, カズユキ; 海老名, 頼利; エビナ, ヨリトシ; 松岡, 憲知; マツオカ, ノリカズ; 豊島, 剛志; トヨシマ, ツヨシ; 大和田, 正明; オオワダ, マサアキ; et al. (1991)
P(論文) 第32次南極地域観測隊(JARE-32)夏隊のセールロンダーネ山地地学調査隊は, 1990年12月24日あすか観測拠点を出発し, 1991年2月7日に再び「あすか」に帰り着くまでセールロンダーネ山地中央部で, 地形・地質・雪氷調査を行い測地作業も実施した。雪上車とスノーモービルを利用してキャンプを移動しながら調査するという従来と同じ行動様式をとったため, 設営面でもおおかたはこれまでの方式と同じである。地学調査は, 地形では, 野外実験地の撤収, 岩石の風化の調査, モレーン・ティルのマッピング, 地質では, 構成岩石の形成順序の解明, 構造地質学的・構造岩石学的そして地球化学的研究のためのサンプリング, 測地では, 重力測量, 地磁気測量, GPSによる基準点測量が行われた。ベルギーからの交換科学者は氷河流動・氷厚などを測定した。 The Sør Rondane field party as part of the summer party of the 32nd Japanese Antarctic Research Expedition (JARE-32) carried out geomorphological, geological, geodetic, and glaciological fieldworks in the central area of the Sør Rondane Mountains for 45 days from December 24,1990 to February 7,1991. The field trip was conducted by two parties, consisting of 9 persons, traveling from mountains to mountains to shift tented camps using 4 snow vehicles towing their equipments on sledges behind. Nine snowmobiles (motor toboggans) were used for their field researches on glaciers. Geomorphologists carried out measurements in the periglacial field experimental sites, observations of rock weathering, and mapping of chronological sequence of tills and moraines. Geologists studied chronological sequence of rock formation and collected rock specimens for structural, petrological, and chemical analyses. A surveyor set up geodetic control stations using GPS satellite positioning system and made gravity surveys on glaciers as well as at some control stations. Two Belgian glaciologists took part in the fieldwork as exchange scientists and studied dynamics of glacier movement and ice thickness. departmental bulletin paper